Effects of Lysophosphatidylcholine on Intestinal Health of Turbot Fed High-Lipid Diets - Sihui Li; Xing Luo; Zhangbin Liao; Mengqing Liang; Houguo Xu; Kangsen Mai; Yanjiao Zhang (Nutrients, 2022)
An 8-week feeding trial was conducted, where turbot were fed four experimental diets, containing different LPC levels (0%, 0.1%, 0.25%, and 0.5%, named LPC0, LPC0.1, LPC0.25, and LPC0.5, respectively). The intestinal morphology results showed that there were no widened lamina propria and mixed inflammatory cells in the LPC-supplemented groups. Dietary LPC remarkably decreased the expression of TLRs (TLR3, TLR8, TLR9, and TLR22), MyD88, and signaling molecules (NF-κB, JNK, and AP-1). Similarly, diets with LPC supplementation markedly depressed the gene expression of NF-κB and JNK signaling pathway downstream genes (TNF-α, IL-1β, Bax, Caspase9, and Caspase-3). Furthermore, dietary LPC modified the intestinal microbial profiles, increasing the relative abundance of short-chain fatty acids-producers, lactic acid bacteria, and digestive enzyme-producing bacteria. Predictive functions of intestinal microbiota showed that turbot fed LPC diets had a relatively higher abundance of functions, such as lipid metabolism and immune system, but a lower abundance of functions, such as metabolic diseases and immune system diseases. The activities of intestinal acid phosphatase and alkaline phosphatase were also increased by dietary LPC. In conclusion, LPC supplementation could regulate the intestinal mucosal barrier via the TLR signaling pathway and alter the intestinal microbiota profile of turbot fed high-lipid diets.